Factors Controlling O+ and H+ Outflow in the Cusp During a Geomagnetic Storm: FAST/TEAMS Observations. Issue 11 (1st June 2020) - Zhao, K.; Kistler, L .M.; Lund, E. J.; Nowrouzi, N.; Kitamura, N.; Strangeway, R. J.
Abstract: Factors related to two sources of energy input to the ionosphere, the Poynting flux associated with both quasistatic fields ( S dc ) and Alfvénic fluctuations ( S ac ), and the soft electron precipitation, are investigated to evaluate their correlations with the O + and the H + outflows in the dayside cusp region by using recalibrated FAST/Time‐of‐Flight Energy, Angle, and Mass Spectrograph (TEAMS) data during the 24–25 September 1998 geomagnetic storm studied by Strangeway et al. (2005, https://doi.org/10.1029/2004JA010829 ). The Poynting flux and the soft electron precipitation are well correlated with ion outflow flux in the dayside cusp region. S dc shows the highest correlation with the O + outflows, while it is the electron number flux that correlates best with the H + outflows. The Alfvénic waves play an essential role in accelerating outflows. The averaged O + /H + flux ratio is 3.0 and is positively correlated to the Poynting flux, suggesting that the O + flux increases more strongly with the energy input. Plain Language Summary: Ionospheric outflows are a major plasma source for the Earth's magnetosphere, especially during geomagnetic storms. Various parameters related to the electromagnetic energy input, the electron precipitation, and the extremely low frequency plasma waves are used to investigate their correlations with ion outflows in the dayside cusp region during the 24–25 September 1998 geomagnetic storm. We first recalibrated the data from the FAST/Time‐of‐Flight Energy, Angle, and Mass Spectrograph (TEAMS) instrument before using it. The electromagnetic energy has the highest correlations with the oxygen ion outflows, while it is the electron precipitation for proton outflows. The energy input associated with Alfvén waves also shows strong correlations. Maxima of the energy input show better correlations than the averages. The oxygen ion is the dominant outflow species in this storm with an average flux ratio of 3.0 to proton outflows. A higher ratio is observed with more energy input to the Earth's ionosphere. Key Points: The best controlling factor for driving O + and H + outflows is quasistatic Poynting flux and soft electron precipitation, respectively The averaged O + /H + flux ratio is 3.0 over the cusp region. The ratio is positively correlated to energy input to the ionosphere The Poynting flux associated with Alfvén waves also shows strong correlation with outflows in the dayside cusp region